Exploring influential factors in selecting halal pharmaceuticals among students (study case IAI Tazkia & University Ibnu Khaldun in Bogor) - Suriedi, Muhammad Ridho Al Fathan; Priantina, Anita (Universitas Ahmad Dahlan, 2024)
Users of halal-certified medicines involve individuals, groups, and organizations; individual actors cannot be separated from students. Several factors influence students who use halal-certified medicines, including attitudes, subjective norms, and purchase intentions. These factors are motivated by the desires and needs of students. This study investigates the impact of knowledge, attitudes, and subjective norms on the purchase intention of halal-certified medicines. The research explores the factors influencing the intention to purchase halal-certified over-the-counter medicines among students at IAI Tazkia and Ibn Khaldun University in Bogor. Data collection primarily comprises primary data. The primary data utilized in this study were gathered by distributing questionnaires to 215 student respondents. This research uses a qualitative methodology and is analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS 3 software with 215 respondents. The results showed that the attitude variables and subjective norms were significantly affected. On the other hand, the knowledge variable was found to have a low influence on the purchase intention of halal medicines among Muslim students, indicating that other factors may play a more significant role in their purchase decisions. Keywords: Attitude, Halal medicine, Purchase intention, Subjective norms